Management of Investment Feasibility in Strengthening the Trigona Bee Cultivation Organization in Bongkasa Pertiwi Village, Abian Semal District, Badung District - Selamet, I Ketut; Rustini, Ni Made; Purnami, A.A Sri (Asian Journal of Management Analytics, 2024)
One of the villages in Bali that is suitable as an area for developing kele-kele (Trigona spp) honey cultivation is Bongkasa Village, Abiansemal, Badung. This condition shows that group management is not good so that in the research year in 2022 there were still 8 active members with a total of 477 colonies. The method used in collecting data for this research is survey and interview methods with primary and secondary data sources. The analysis technique used is Payback Period (PBP), Net Present Value (NPV) analysis. With indicators measuring interest rates and net cash inflow compared to investment, getting a positive NPV of IDR 800,390,453 means that the investment is worth continuing, even on a larger scale